ANALISIS KARAKTER DALAM MODUL BUPENA TERBITAN ERLANGGA KELAS IV BERDASARKAN KURIKULUM 2013 - Retnosari, Yeni; , Muhroji, M.Si., M.Pd., S.E (2017)
This study aimed to describe the module bupena issue grants, analysis of the suitability of the values of character, and the characters often appear. This study used a qualitative descriptive approach and is the type of research literature. Data collection techniques using methods refer to. While the validity of the data using enhanced persistence and data analysis techniques using content analysis. The results showed that: (1) Module Publication BupenaErland Class IV at 4 Various themes and themes Works 5 Heroes are deepening matter, a matter of evaluation, performance skills practice, and product performance skills. The modules section contains the values of the characters to be developed. (2) Overall both themes that were analyzed showed the emergence of all the character values in accordance with the Regulation of the Minister of Education and Culture No. 64 Year 2013 on the Content Standards for Primary and Secondary Education. The values of these characters other anta: religious values, honesty, discipline, responsibility, decency, kepeduliaan, and confident. But the spread of the characters in this module are less prevalent, there is a character who often appears, there are only a few times appear not even appear on each sub-theme. (3) There are three grades of character with the highest frequency value is self-confidence, discipline, and responsibility. The value of this character has been spread evenly on each sub-theme in theme 4 and 5 theme